The Multilocation Multiperiod Inventory Problem: Bounds and Approximations - Karmarkar, Uday S. (Management Science, 1987)
The multilocation inventory problem can be thought of naturally as an extension of the single location “newsboy” problem to multiple locations with transshipment possible between locations. Previous work has established the form of optimal policies; however, computational results have been limited to the one-period case or to special structures. This paper develops lower- and upper-bounds for the general multiperiod problem. These also suggest approximations to the optimal solution. Computational methods are discussed and tested on small problems.